Hadith #12 - The Forty Hadith Qudsi - Abu Mas'ud al-Ansari (The Forty Hadith Qudsi)
On the authority of Abu Mas’ud al-Ansari (may Allah be pleased with him), who said that the Messenger of Allah (may the blessings and peace of Allah be upon him) said: A man from among those who were before you was called to account. Nothing in the way of good was found for him except that he used to have dealings with people and, being well-to-do, he would order his servants to let off the man in straitened circumstances [from repaying his debt]. He (the Prophet p.b.u.h) said that Allah said:
Grade: Sahih